Comparative Study of Financial Performance in Two Non-Banking Sector Companies: Liquidity, Solvency, Profitability, and Activity Ratio Approach - Nurman (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
This study aims to compare the financial performance of two non-banking sector companies listed on the Indonesia Stock Exchange (IDX), using financial ratio analysis including liquidity, solvency, profitability, and activity ratios. Data were obtained from annual financial reports for the period 2019 to 2023. The analysis method used is quantitative descriptive with a comparative approach. The results of the study show significant differences in the financial performance of the two companies, especially in the profitability and activity ratios, which are influenced by the operational efficiency and capital structure of each company. These findings provide an overview for investors and management in evaluating performance and making strategic decisions.